Decision making in soccer: effect of positional role of U-13 soccer players - Andrade, L.; Machado, G.; Goncalves, E.; Teoldo, I. (Journal of Physical Education and Sport, 2021)
Introduction: Making efficient decisions is an important characteristic for athletes to achieve superior performance in soccer. Due to the highly demanding environment of soccer, different functions are necessary to enable superior collective performance. With respect to the assessment of decision making according to playing positions, no studies have yet been carried out to assess the contents of the core tactical principles, and thus further investigations are necessary to address this issue. Objective: The aim of this study is to verify the influence of positional role on the decision-making skills of U-13 soccer players. Methods: Thirty U-13 male soccer players (12.9 ± 0.7 y/o) from regional soccer schools participated in this study. Players were classified according to three positional roles: defenders (n = 9), midfielders (n = 11) and forwards (n = 10). The instrument used to assess players` decision-making skills and decision-making time was the TacticUP® online platform. This instrument assesses the quality and time of decision making based on the core offensive and defensive tactical principles of soccer, in situations near and distant from the ball. Descriptive analysis, as well as the Shapiro-Wilk, ANOVA and Tukey`s post-hoc tests were performed, and effect sizes were reported as eta-squared (p< 0.05). Results: Findings did not show differen ces in decision-making quality between the different positional roles. As for decision-making time, midfielders made quicker decisions, when compared to defenders and forwards, in situations near and distant from the ball (p < 0.05). Conclusions: It is concluded that positional role influenced the decision-making time of U-13 soccer players. In general, midfielders displayed greater ability to read the game and make quicker decisions when compared to defenders and forwards in offensive and defensive situations near and distant from the ball. Therefore, it implies that to fulfil the role/function of midfielder in the field, in addition to being assertive, players also have to be quick in making decisions.